Developing and validating the Dragons of Inaction Psychological Barriers (DIPB) scale. (June 2019) - Lacroix, Karine; Gifford, Robert; Chen, Angel
Abstract: The Dragons of Inaction Psychological Barrier (DIPB) scale, a measure of psychological barriers, was developed and validated in three studies across six environmental domains: food choices, transportation, energy use, water use, purchasing, and waste. A preliminary 65-item version was created based on past studies. In Study 1, it was examined using a large sample with exploratory factor analysis; five factors emerged. In Study 2, using a different sample, the factors were supported with confirmatory factor analyses. In Study 3, measurement invariance of the scale was supported across high and low difficulty behaviors. The final 22-item DIPB includes five subscales: Change Unnecessary, Conflicting Goals and Aspirations, Interpersonal Relations, Lacking Knowledge, and Tokenism. No significant DIPB differences across environmental domains were found for Tokenism, but the Change Unnecessary barrier was weakest for buying green, whereas the Interpersonal Relations barrier was strongest for food choices, the Conflicting Goals and Aspirations barrier was strongest for driving less, and the Lacking Knowledge barrier was strongest for buying green. Highlights: The Dragons of Inaction Psychological Barrier (DIPB) scale was developed and validated. The barrier structure was confirmed in the six major domains of pro-environmental behavior. The relative importance of each psychological barrier factor varied across domains of behavior. The DIPB will help identify which context-specific psychological barriers are most problematic.